ANALYSIS OF MATHEMATICAL MISCONCEPTIONS IN NUMBERS MATERIAL IN CLASS V PRIMARY SCHOOL - Elsa Chaeratunnisa; Hepsi Nindiasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mathematics learning plays an important role in developing students' critical, logical and systematic thinking abilities. However, the abstract nature of mathematics often causes misconceptions, especially regarding the concept of exponent numbers. This research aims to identify misconceptions of fifth grade elementary school students in understanding numbers with powers and the factors that cause them. This research uses descriptive qualitative methods, this research involves 30 students as participants, with a focus on in-depth analysis of three students. Data was obtained through observation, tests and semi-structured interviews. The research results show that students often misunderstand the basic concept of exponent numbers, such as considering exponents as ordinary additions or misunderstanding powers of zero and powers of one. Factors causing misconceptions include limited student understanding, less contextual teaching methods, and cultural and linguistic influences. To overcome this misconception, a more effective teaching approach is needed, such as the use of concrete visualizations (for example, squares for cubes and cubes for cubes) and the application of interactive methods that are relevant to everyday life. This research provides recommendations for teachers to improve learning strategies and encourages further research to develop innovative methods in teaching exponent numbers. In this way, students are expected to be able to understand mathematical concepts in depth and correctly, which will have an impact on improving their learning outcomes.